Integrated Approach to Estimate Land Use Intensity for Hungary - Mezősi, Gábor; Meyer, Burghard C.; Bata, Teodóra; Kovács, Ferenc; Czúcz, Bálint; Ladányi, Zsuzsanna; Blanka, Viktória (Journal of Environmental Geography, 2019)
An integrated approach was applied in this article to provide a medium-scale map of land use intensity for Hungary. The main goal was to estimate its value by a small set of parameters, which are freely available and have a high resolution. The basis of the evaluation was the CORINE 2012 dataset, and a matrix method was applied to integrate the ratio of natural/semi-natural vegetation, woody vegetation and the Natural Capacity Index in the assessment to describe the complex approach of land use intensity. The medium level land use intensity map provides information for decision makers/landscape planners on the current status and spatial pattern of anthropogenic impact and indicates those hot-spots where land use intensity is high and should be focused research and management to intervene in order to encourage sustainable land use. 46% of the arable lands in Hungary show the most intensive land use. Comparing the map with the previously published hemeroby map of Hungary, more intensive impact on landscape transformation through human action was found. In agricultural areas both researches agree that the intensity and human activity is really high, and the lowest intensity class is rare in Hungary except for mountain regions and protected areas.